Analysis of ameloblastic fibroma lesion on panoramic radiograph: a case report - Muchlis, Muhammad Rakhmat Ersyad; Firman, Ria Noerianingsih; Epsilawati, Lusi (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2024)
Objectives: This case report aims to present a case of ameloblastic fibroma, an odontogenic tumor, and to describe its characteristic radiographic features as observed on a panoramic radiograph. Case Report: A 28-year-old woman presented to the RSGM FKG Unpad with a referral for evaluation of a jaw swelling. According to the patient’s medical history, the swelling had gradually appeared over the past two years. While it was not painful, it caused discomfort, prompting her to seek medical attention. Upon examination, the lesion was found in the posterior region of the mandible, and further diagnostic imaging was recommended to determine the extent and nature of the lesion. Ameloblastic fibroma of the jaw is a benign, relatively rare, mixed odontogenic tumor whose epithelial and mesenchymal components are neoplastic. This tumor is usually diagnosed in the first and second decades of life (72.4%), when odontogenesis has been completed (80% of cases), and mainly affects the mandible. In this case, the lesion was diagnosed in the second decade of life, and occurred in the posterior region of the mandible. Conclusion: Ameloblastic fibroma is a benign odontogenic mixed tumor, although rarely ameloblastic fibroma can recur and develop into malignancy. The aim of this case report is to analyze the radiographic appearance of the lesion with information from the history and clinical signs to establish a correct radiodiagnosis.